# how to solve the following equation

How to solve (3x-4)=(4x-3)2

3x-4 = (4x - 3 ) 2=> 3x-4 = (4x - 3 ) * 2=> 3x-4 = ( 4x * 2 )  -  ( 3  * 2 )=> 3x-4 = 8x - 6=> 3x- 8x = 4-6=> -5x = -2=> 5x = 2=> x = 2/5
sudhansu
13 January 2019
When getting such questions, always expand the brackets first. Then move all x to one side of the equation(3x-4)=(4x-3)2Step one: 3x-4=8x-6Step two: 2=5xx=2/5
Paul T.
15 January 2019
(3x-4)=(4x-3)23x-4=8x-63x-8x=-6+4-5x=-2x=2/5
nitheesh
18 January 2019
(3x - 4) = (4x - 3) 2 3x - 4 = 2*4x - 2*3 3x - 4 = 8x - 66 - 4 = 8x - 3x2 = 5x x = 2/5
drqazi
21 January 2019
3x-4=8x-6-4=5x-62=5x2/5=x
samleej4
27 January 2019
multiplying the brackets on the right side we get:3x-4=8x-6We have to try to bring x to one side and numbers to the other. So we add 6 both sides. We get:3x+2=8xNow we have to minus 3x.2=5xnow we need to divide by 5, to get x, therefore x is:x=2/5
prashasti
29 January 2019
(3x-4)=(4x-3).2 3x-4=8x-63x-8x=-6+4-5x=-2x=-2/(-5)x=2/5 you need to change the signs when to put the numbers on the other side.the opposite of + is - and the opposite of multiplication is division.
eduarda
07 February 2019
So to solve (3x-4) = (4x-3)2 the first thing I would do is expand the brackets / multiply the brackets on the right hand side of the equation which would give us:3x-4 = 8x - 6The next thing i would do is bring the x’s on one side and the numbers on the other. So in this case I will bring the 3x over to the right side by misusing 3x on both sides, and I will bring the 6 over to the left side by adding 6 on both sides, which would give us:2 = 5xTo find x we can the divide both sides by 5 which would give us:X = 2/5
drishti.a
29 April 2019
5
HEMRAJ GURJAR
10 March 2021